2021
DOI: 10.1177/1753466620971141
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-tract infections among geriatrics: prevalence and factors associated with the treatment outcomes

Abstract: Background: Geriatric individuals are more susceptible to different infections, especially respiratory-tract infections (RTIs) due to their compromised immune system. Hence, the objectives of the present study were to evaluate the prevalence, medication regimen complexity and factors associated with the treatment outcomes of different RTIs among geriatrics. Methods: A retrospective cross-sectional study (5 years) was conducted at the respiratory department, Hospital Pulau Pinang. Patients aged ⩾65 years with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Some recent reports showed the relationship between polypharmacy and pneumonia, but did not evaluate frailty or disability. 21,22 In this regard, we consider the present report to be novel. Previous studies have reported the association of the use of benzodiazepines, antipsychotics and anticholinergics with pneumonia.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some recent reports showed the relationship between polypharmacy and pneumonia, but did not evaluate frailty or disability. 21,22 In this regard, we consider the present report to be novel. Previous studies have reported the association of the use of benzodiazepines, antipsychotics and anticholinergics with pneumonia.…”
Section: Discussionmentioning
confidence: 60%
“…There are few reports that tried to clarify the association between polypharmacy and pneumonia. Some recent reports showed the relationship between polypharmacy and pneumonia, but did not evaluate frailty or disability 21,22 . In this regard, we consider the present report to be novel.…”
Section: Discussionmentioning
confidence: 61%
“…The reported mean MRCI score in this study was 17.38 (SD = 7.07), which can be categorized into medium complexity (15.5–20) [ 20 ]. In comparison, two studies that evaluated MRC among Malaysian older adults diagnosed with acute infections (i.e., UTI and RTI) reported low complexity (≤ 15.0), which were 14.0 and 11.8, respectively [ 34 , 35 ]. Other studies also evaluated MRC among chronic kidney disease (CKD) older patients in Australia and Norway, with reported higher MRCI scores of 27.0 and 22.8, respectively, which are classified as high complexity (≥ 20.5) [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is uncertain how much pneumococcal vaccines may prevent more nonspecific outcomes such as lower respiratory tract infections (LRTI) [7][8][9]. A large proportion of acute respiratory tract infections (ARI) lead to antibiotic prescriptions, with ARIs accounting for an estimated 50% of all antibiotic prescriptions in adults [10][11][12]. As a reduction in antibiotic use is likely to help to curb the global emergence of antimicrobial resistance, it is also important to quantify whether pneumococcal vaccination has any role in reduction of ARI presentations and subsequently ARI-related antibiotic prescriptions, and no previous study has yet investigated this in adults.…”
Section: Introductionmentioning
confidence: 99%